2000
DOI: 10.1093/genetics/154.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Nrf1p, a Novel Negative Regulator of the Cdc42p GTPase in Schizosaccharomyces pombe

Abstract: The Cdc42p GTPase and its regulators, such as the Saccharomyces cerevisiae Cdc24p guanine-nucleotide exchange factor, control signal-transduction pathways in eukaryotic cells leading to actin rearrangements. A cross-species genetic screen was initiated based on the ability of negative regulators of Cdc42p to reverse the Schizosaccharomyces pombe Cdc42p suppression of a S. cerevisiae cdc24ts mutant. A total of 32 S. pombe nrf (negative regulator of Cdc forty two) cDNAs were isolated that reversed the suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…In contrast, evening types perform well in the evening hours (4) and seem to tolerate elevated sleep pressure in the evening better than morning types. Besides differences in circadian phase (5-8), morning types differ from evening types by a faster build-up of homeostatic sleep pressure during daytime (9) and by its faster dissipation during sleep (10,11). Taken together, these results support the notion that the circadian variation in waking performance also depends on homeostatic sleep pressure (2,12,13).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In contrast, evening types perform well in the evening hours (4) and seem to tolerate elevated sleep pressure in the evening better than morning types. Besides differences in circadian phase (5-8), morning types differ from evening types by a faster build-up of homeostatic sleep pressure during daytime (9) and by its faster dissipation during sleep (10,11). Taken together, these results support the notion that the circadian variation in waking performance also depends on homeostatic sleep pressure (2,12,13).…”
supporting
confidence: 57%
“…Genetic screens in yeast yielded ≥250 alternative candidates whose deletion decreases cellular polyP (8,9), but the identity of the polyP-synthesizing enzyme has remained elusive. Among the candidates is the yeast vacuolar transporter chaperone (VTC) complex, a membrane protein assembly whose deletion reduces polyP accumulation (8) but also affects membrane transport and vesicular traffic (10)(11)(12). We have used x-ray crystallography to identify a polyP polymerase in VTC.…”
mentioning
confidence: 99%
“…A genomic functional analysis approach showed that an insertion mutation in VTC1 leads to slow growth (Smith et al ., 1996). Overexpression of the protein is lethal in Schizosaccharomyces pombe (Murray and Johnson, 2000). Vacuoles in all deletion strains except vtc2Δ showed abnormal morphology, indicating that vacuole biogenesis was disturbed.…”
Section: Resultsmentioning
confidence: 99%
“…The Cdc42 GTPase is involved in many aspects of growth and cell-cycle regulation, including actin cytoskeletal rearrangements and activation of signal transduction pathways (Sections 4, 6 and 7) [78]. In fission yeast, lack of Cdc42 essential function results in arrested small and round uninucleate cells with mislocalized actin that cannot mate [4,129]. Unlike budding yeast, expression of constitutively active cdc42 alleles in S. pombe is not lethal, but it results in an abnormal morphological phenotype of large, round or misshapen cells with delocalized cortical actin structures (Table 1) [4,130].…”
Section: Cdc42mentioning
confidence: 99%